Avaliação microbiológica de alimentos da culinária japonesa, comercializadas em Botucatu, SP - Silva, Gousilin Leandra Rocha da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The search for a healthy lifestyle has been increasing and reaching more and more individuals looking for foods that suit this aspect, such as Japanese cuisine. Although the dishes are considered beneficial to health, the highly perishable characteristic, due to the presence of raw fish, combined with a preparation with high handling, increases the risks of contamination. Thus, considering the risks of contamination and the scarcity of information on the hygienic-sanitary quality of Japanese cuisine foods in the city of Botucatu, the objective was to verify the microbiological quality of Japanese cuisine foods, according to the standards established by RDC No. 12/2001 (ANVISA), with the investigation of Bacillus cereus, coagulase-positive Staphylococcus (CPS), Salmonella sp and Vibrio parahaemolyticus, in addition to the determination of thermotolerant coliforms (CTo). Despite not being part of this legislation, coagulas-negative staphylococci (CNS) were also investigated. The CPS isolates were identified up to the species S. aureus by PCR, in addition to the investigation of the presence of genes coding for the production of biofilm and some enterotoxins (SEA-SEI). In addition, the in vitro production of biofilm and classical enterotoxins (SEA-SED) were tested. Among the 70 samples analyzed, from 14 restaurants in Botucatu/SP, 50 (71.4%) presented CTo, but only 27 (38.6%) were above the established limits. Salmonella sp, V. parahaemolyticus and B. cereus were not detected. S. aureus was observed in 5 (7.1%) samples. Regarding the genes encoding enterotoxins, the seg and sei gene were the most frequent, being present simultaneously in 2 (40%) isolates, seh was also observed in 2 (40%) isolates and the classical enterotoxin genes were not detected. All S. aureus strains were moderate biofilm producers. The icaD gene was present in all isolates and icaA in 40%. Even with the absence of diarrhea-causing bacteria such as Salmonella sp, V. parahaemolyticus and B. cereus, Japanese food sold in Botucatu/SP cannot be considered safe for consumption, due to the presence of CTo, which indicates contamination of faecal origin. In addition, there was the presence of S. aureus, a bacterium with enterotoxigenic potential, and of CNS which, as they are part of the human skin microbiota, demonstrate a lack of hygiene on the part of the handlers.

A busca por um estilo de vida saudável vem aumentando e atingindo cada vez mais indivíduos que procuram alimentos que se adequem a esse quesito, como os da culinária japonesa. Apesar dos pratos serem considerados benéficos a saúde, a característica altamente perecível, pela presença do peixe cru, aliado a um preparo com elevada manipulação, aumenta os riscos de contaminação. Assim, considerando os riscos de contaminação e a escassez de informações sobre a qualidade higiênico-sanitária de alimentos da culinária japonesa na cidade de Botucatu, o objetivo foi verificar a qualidade microbiológica de alimentos da culinária japonesa, de acordo com os padrões estabelecidos pela RDC No 12/2001 (ANVISA), com a pesquisa de Bacillus cereus, Staphylococcus coagulase positiva (ECP), Salmonella sp e Vibrio parahaemolyticus, além da determinação de coliformes termotolerantes (CTo). Apesar de não fazer parte dessa legislação, os estafilococos coagulase negativa (ECN) também foram pesquisados. Os isolados de ECP foram identificados até a espécie S. aureus por PCR, além da pesquisa da presença dos genes que codificam para a produção de biofilme e de algumas enterotoxinas (SEA- SEI). Além disso, foram testadas a produção in vitro de biofilme e das enterotoxinas clássicas (SEA-SED). Entre as 70 amostras analisadas, de 14 restaurantes de Botucatu/SP, 50 (71,4%) apresentaram CTo, mas somente 27 (38,6%) estavam acima dos limites estabelecidos. Salmonella sp, V. parahaemolyticus e B. cereus não foram detectados. S. aureus foi observado em 5 (7,1%) amostras. Em relação aos genes que codificam as enterotoxinas, o gene seg e sei foram os mais frequentes, estando presentes simultaneamente em 2 (40%) isolados, o seh foi observado também em 2 (40%) isolados e os genes das enterotoxinas clássicas não foram detectados. Todos as cepas de S. aureus foram produtores moderados de biofilme. O gene icaD esteve presente em todos os isolados e o icaA em 40%. Mesmo com a ausência de bactérias causadoras de diarreias como Salmonella sp, V. parahaemolyticus e B. cereus, os alimentos da culinária japonesa comercializados em Botucatu/SP não podem ser considerados seguros para o consumo, devido à presença de CTo, que indicam contaminação de origem fecal. Além disso, ocorreu a presença de S. aureus, bactéria com potencial enterotoxigênico, e de ECN que, por fazerem parte da microbiota da pele de humanos, demonstram falta de higiene por parte dos manipuladores.
Microbiological evaluation of Japanese cuisine foods, sold in Botucatu, SP
Keywords: Japanese cuisine; Biofilm; Enterotoxins; Culinária japonesa; S. aureus; Salmonella; V. parahaemolyticus; Biofilme; Enterotoxinas; RPLA